2012
DOI: 10.1111/j.1600-0706.2011.20258.x
|View full text |Cite
|
Sign up to set email alerts
|

To resprout or not to resprout: factors driving intraspecific variability in resprouting

Abstract: Resprouting is a mechanism that allows individual plants to persist in disturbance‐prone ecosystems. It is often considered a binary trait, defining species as resprouters or non‐resprouters. Although this dichotomous classification accounts for a high proportion of the interspecific variability in resprouting, it does not account for the intraspecific variability, as not all individuals of resprouting species successfully resprout, even if they are subject to a similar disturbance. To ascertain the causes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 49 publications
4
100
0
7
Order By: Relevance
“…Fang et al [42], studying regrowth ecophysiology, describe a decrease in TSS concentrations during the regrowth process, wherein root tissues became the source in a source-sink system. This agrees with other studies that have concluded that a capacity to mobilize such reserves, and so support sprouting shoot growth, is predominant in the period following pollarding [34,36,[75][76][77].…”
Section: Rosewood Shoots Following Above-ground Biomass Managementsupporting
confidence: 82%
See 2 more Smart Citations
“…Fang et al [42], studying regrowth ecophysiology, describe a decrease in TSS concentrations during the regrowth process, wherein root tissues became the source in a source-sink system. This agrees with other studies that have concluded that a capacity to mobilize such reserves, and so support sprouting shoot growth, is predominant in the period following pollarding [34,36,[75][76][77].…”
Section: Rosewood Shoots Following Above-ground Biomass Managementsupporting
confidence: 82%
“…The post-harvest regrowth capacity of a tree is influenced by such factors as pre-disturbance condition [32,33], initial capacity to acquire post-disturbance resources, genetic predisposition [34], as well the dormant seedbank [35]. In rosewood, vigorous regrowth of managed trees has been reported [6,7,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to support respiratory demands and initiate sprouting, such plants shall have sufficient carbohydrates and nutrients stored in their underground organs (Bowen & Pate 1993). Moreira et al (2012) while studying factors driving intraspecific variability in sprouting, found that resources stored by the plant pre-disturbance can boost its initial ability to sprout and the sprouting vigor and, consequently, its initial post-disturbance ability to acquire new resources. Likewise, the development of root buds depends on the resources stored by the main trunk.…”
Section: Resultsmentioning
confidence: 99%
“…Following other studies (e.g., Andeires et al, 2002;Van Langevelde et al, 2003;Beckage et al, 2009;Yu and D'Odorico, 2014a), the rate of change of shrub biomass is proportional to the existing shrub biomass, S, and to the resources available for new shrub growth, Smax-S, while fireinduced disturbance kills shrubs at a rate that is proportional to the existing shrub biomass and to fire frequency, , Consistent with other studies (e.g., Andeires et al, 2002;Van Langevelde et al, 2003;Yu and D'Odorico, 2014a), this model does not account for resprouting of shrubs after fires, a trait that is species-specific and is expected to favor State II (e.g., Chidumayo, 2004;Vest et al, 2004;Moreira et al, 2012). Thus, grasses may limit shrub growth only through fire dynamics but not through a preferential access to the available resources.…”
Section: Vegetation Dynamicssupporting
confidence: 70%